Introducing the Systemic Approach to Early Education. Issue 2 (24th February 2016) - Roth, Ian M.; Roth, William F.
Abstract : The United States is lagging behind the rest of the developed world in adopting systemic thinking as a means of dealing with societal issues. Such thinking is introduced only in the late stages of our educational process, if at all. The article presents an argument for introducing it at the primary and secondary levels of the education hierarchy, discusses the value of such an approach, and offers a model for doing so.